Biomechanics of the knee extensor mechanism and its relationship to patella tendinopathy: A review. Issue 12 (5th September 2018) - Dan, Michael; Parr, William; Broe, David; Cross, Mervyn; Walsh, William R.
ABSTRACT: The term jumpers knee for patella tendinitis, as coined by Dr. Martin Blazina, is now commonly referred to as tendinopathy. He believed it was associated with patella alta. Since then multiple studies have failed to reliably show an association between patella tendinopathy and associated intrinsic risk factors. There is, unfortunately, a well‐established doctrine that the extensor mechanism is simply a pulley. The goal of the review is to examine the biomechanics of the extensor mechanism and apply this to studies investigating intrinsic risk factors for patella tendinopathy. A better understanding of the biomechanics of the extensor mechanism may stimulate the discovery of intrinsic risk factors for developing patella tendinopathy, and subsequent surgical options to address them. Clinical significance: The aim of this review is to direct future research into biomechanical risk factors for developing patella tendinopathy and subsequently, possible treatments. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:3105–3112, 2018.